Disruptive behavior disorders - Leventhal, Bennett L.; Tolan, Patrick H. (Advances in Development and Psychopathology: Brain Research Foundation Symposium Series, 2013)
Aggressive behavior among children and adolescents has confounded parents and perplexed professionals-especially those tasked with its treatment and prevention-for countless years. As baffling as these behaviors are, however, recent advances in neuroscience focusing on brain development have helped to make increasing sense of their complexity. Focusing on their most prevalent forms, Oppositional Defiant Disorder and Conduct Disorder, Disruptive Behavior Disorders advances the understanding of DBD on a number of significant fronts. Its neurodevelopmental emphasis within an ecological approach offers links between brain structure and function and critical environmental influences and the development of these specific disorders. The book's findings and theories help to differentiate DBD within the contexts of normal development, non-pathological misbehavior, and non-DBD forms of pathology. Throughout these chapters are myriad implications for accurate identification, effective intervention, and future cross-disciplinary study. Key issues covered include: Gene-environment interaction models. Neurobiological processes and brain functions. Callous-unemotional traits and developmental pathways. Relationships between gender and DBD. Multiple pathways of familial transmission. Disruptive Behavior Disorders is a groundbreaking resource for researchers, scientist-practitioners, and graduate students in clinical child and school psychology, psychiatry, educational psychology, prevention science, child mental health care, developmental psychology, and social work.